The Effort of Counseling Guidance Teacher in Overcoming Student Fights at SMPN 14 Pekanbaru - Ricky Meyrizal; Kasmanto Rinaldi (AMIN: International Journal of Islamic Education and Knowledge Integration, 2023)
Schools not only teach various sciences, but also educate and direct student behavior from bad to better, so that it is hoped that students will have good character and achieve the goals of national education. The formulation of the problem in this study is how the counseling guidance teacher's efforts in overcoming student fights are reviewed from the standard of counseling guidance services at the secondary school level at SMPN 14 Pekanbaru in 2017. The type of research in this study is included in qualitative research with the aim of describing the actual situation that occurs at the research location through collecting, identifying, and analyzing data so that an answer to the problem is formulated. Key informants in this research are Principal of SMPN 14 Pekanbaru, BK Teacher of SMPN 14 Pekanbaru, while informants are Students who fight, Head of Osis, parents of students, Alumni of SMPN 14 Pekanbaru, community around SMPN 14 Pekanbaru, and School guards. In this study examines the situational crime prevention strategy theory approach. This research shows the lack of efforts made by the school in overcoming student fights where efforts are made only when after the fight occurs not before the fight occurs. Efforts made in the form of making a statement letter, summoning parents and saluting the flag in the field.